Servqual Analysis on Merangin Public Library Services, Jambi Province - Hapsari, Rian Dwi; Seftiawan, Ahmad Berri; Umanah, Umanah (Department Library of Governance Institut of Home Affairs, 2020)
Problem Statement: The author focuses on the gap in demands for good service quality, but it is not supported by human resources and the availability of professional librarians who oversee library services in Merangin Regency. Purpose: The purpose of this article is to find out the quality of library services in the public library of Merangin Regency. Method: The writer uses descriptive method and inductive approach. Data obtained and collected through interviews, observation, and documentation. Furthermore, the data that has been collected is analyzed using data reduction techniques, data display (data presentation) and conclusions. Result: The research findings show that the dimensions of tangible and reliability are still lacking, then the dimensions of empathy, responsiveness and assurance are classified as sufficient (standard). Conclusion: The results show that the service quality of the Merangin Public Library is still not optimal. This is because in the dimension of service quality, there are several indicators that are still in the insufficient category, namely service support facilities, non-updated collections, inadequate employee resources, and information related to libraries that are still not widely known by the public. Keywords: : Servqual Analysis; Quality of Services; Public Library Services; Merangin Public Library